2012
DOI: 10.1258/jtt.2012.120219
|View full text |Cite
|
Sign up to set email alerts
|

Twenty years of telemedicine in chronic disease management – an evidence synthesis

Abstract: A literature review was conducted to obtain a high-level view of the value of telemedicine in the management of five common chronic diseases (asthma, COPD, diabetes, heart failure, hypertension). A total of 141 randomised controlled trials (RCTs) was identified, in which 148 telemedicine interventions of various kinds had been tested in a total of 37,695 patients. The value of each intervention was categorised in terms of the outcomes specified by the investigators in that trial, i.e. no attempt was made to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
381
0
18

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 468 publications
(408 citation statements)
references
References 33 publications
9
381
0
18
Order By: Relevance
“…Despite these encouraging results, the penetration of these technological advances in the clinical practice is still slow, especially when compared with other respiratory chronic diseases or others pathologies [98,99,[101][102][103]. Furthermore recently published results questioned the validity of this technology as a method to delivery healthcare for all populations [104].…”
Section: Role Of Tele-monitoring In Sleep-related Breathing Disordersmentioning
confidence: 99%
“…Despite these encouraging results, the penetration of these technological advances in the clinical practice is still slow, especially when compared with other respiratory chronic diseases or others pathologies [98,99,[101][102][103]. Furthermore recently published results questioned the validity of this technology as a method to delivery healthcare for all populations [104].…”
Section: Role Of Tele-monitoring In Sleep-related Breathing Disordersmentioning
confidence: 99%
“…Terms like telecare, telehealth, telemedicine, eHealth and mHealth are used interchangeably, and various definitions of these concepts exists [17,34,44].…”
Section: Ehealthmentioning
confidence: 99%
“…One review of telehealth-assisted chronic disease management (Wootton 2012) identified three diabetes trials in which patients whose management included videoconferencing had significantly better blood glucose levels. The results for heart failure were less conclusive; several studies found fewer hospitalisations and higher quality of life, but the differences were not always significant.…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…The results for heart failure were less conclusive; several studies found fewer hospitalisations and higher quality of life, but the differences were not always significant. Wootton (2012) concluded that 'the evidence base for telemedicine in managing chronic diseases is on the whole weak and contradictory'. Overall, the available evidence indicates that outcomes of video consultations are not significantly different from outcomes of FTF consultations for most conditions and specialties.…”
Section: Clinical Applicationsmentioning
confidence: 99%